Exploring Natural Products as a Source for Antidiabetic Lead Compounds and Possible Lead Optimization - Abu Khalaf, Reema (Current Topics in Medicinal Chemistry, 2016)
Background: Natural products are characterized by their chemical diversity and being a good source of a range of bioactive structures including antidiabetic compounds. Diabetes mellitus (DM) is considered a major worldwide health concern. Rational drug design has been widely accomplished, to discover and optimize innovative leads for different molecular targets of type 2 DM including α-glucosidase, PPARγ, DPP-IV, PTP1B, AR, GSK-3β, 11β-HSD1, GK, etc. Objective: This review illustrates the potential of natural products as a rich source of lead compounds for antidiabetic drug discovery with some examples of computational studies carried out to determine the possible molecular target, structure activity relationship, and further optimization chances. Conclusion: Natural products will remain an attractive source for researchers to explore their therapeutic potential against DM. Guided by the computational studies; systematic lead optimization via structural modifications will speed up the generation of potential new clinical candidates for the treatment of type 2 DM.
Keywords: Natural lead